A Systematic Mapping of the Use of Games for Teaching Programming - Lima, Maurício; Ferreira, Deller; Dias, Elisângela Silva (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2025: Anais do XXII Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2025.14246, 2025)
The integration of digital games in programming education is an approach aimed at overcoming challenges such as high dropout rates and learning difficulties in this subject. This systematic mapping examines digital games applied to programming learning through the analysis of 19 selected studies from a total of 1143. The results highlight that digital games not only significantly increase student engagement, but also improve their understanding of fundamental programming concepts. Games offer a playful and interactive form of learning, enabling a more engaging and effective educational experience. This study contributes to the field of technology education by demonstrating how digital games can be effectively used to teach programming, suggesting a potential reduction in dropout rates and an improvement in the quality of learning in technical and engineering courses. The review also identifies a significant gap in the literature on the potential disadvantages of using games in educational environments, highlighting the need for future research in this area.